Spatial Soundscapes and Virtual Worlds: Challenges and Opportunities - Rajguru, Chinmay; Obrist, Marianna; Memoli, Gianluca (Frontiers in Psychology, 2020)
There is increasing effort to characterize the soundscapes around us so that we can design more compelling and immersive experiences. This review paper focuses on the challenges and opportunities around sound perception, with a particular focus on spatial sound perception in a virtual reality (VR) cityscape. We review how research on temporal aspects has recently been extended to evaluating spatial factors when designing soundscapes. In particular, we discuss key findings on the human capability of localizing and distinguishing spatial sound cues for different technical setups. We highlight studies carried out in both real-world and virtual reality settings to evaluate spatial sound perception. We conclude this review by highlighting the opportunities offered by VR technology and the remaining open questions for virtual soundscape designers, especially with the advances in spatial sound stimulation.